Role of editing of R-R intervals in the analysis of heart rate variability - Peltola, Mirja (Frontiers in Physiology, 2012)
Measurement of the heart rate (HR) variability from short and long-term electrocardiographic (ECG) recordings is a non-invasive method, which can used be as a tool to evaluate cardiac autonomic regulation. HR variability can give information about the sympathetic-parasympathetic autonomic balance. One important clinical application is to measure HR variability from patients suffering acute myocardial infarction (AMI). However, HR variability signals, R-R interval time series obtained from ambulatory ECG recordings contain in most of the cases different amount of artefacts. Artefacts appear due to disturbances of either physiological or technical origin. For instance, technical artefacts may result from poorly fastened electrodes or be due to motion artefacts. Ectopic beats and atrial fibrillation are examples of biological artefacts. Since the ectopic beats and other artifacts are common phenomena in the R-R interval time series, they make a reliable analysis of the HR variability difficult or even impossible. In conjunction with the increased usage of HR variability analyses, various studies have confirmed the need of different approaches to handle artefacts in the R-R interval time series. The editing process of the R-R interval time series has become an important part of the HR variability analysis. Several different editing and HR variability signal preprocessing methods have been introduced and tested for the artefact correction. Artifact correction can be performed with different methods such as deletion, various interpolation methods and different filtering systems. However, different editing methods can have different effects on the HR variability measures. The effects of editing is depended on the study setting including the editing method, HR variability measure, type of study population, length of the R-R interval time series.